"We're Talking About You, Not to You": Methodological Reflections on Public Health Research With Families With Young Children. (October 2020) - Eastham, Rachael; Kaley, Alexandra
In this article, we critically reflect upon the experience of public health research involving children and contribute to existing conversations about the methodological and ethical facets of research in this field. Drawing on two phases of a study that sought to explore the lived experiences of families with young children who have had a recent common childhood illness (gastrointestinal infection), we address the research process, from inception of the studies, to fieldwork and the resultant material obtained. We argue that when researching with families about a child-centered experience, it is important to look beyond the individual adult as "participant" and to conceptualize dependents either as, or "like" participants—what we suggest as a "family-centered approach." Theoretically, this strategy best addresses the lived reality of relationality and responsibility of parent/carers for dependent children; while improving the ease and safety of data collection for the researcher and participants alike.